2013
DOI: 10.1039/c3cc38769k
|View full text |Cite
|
Sign up to set email alerts
|

Reversible switching between self-assembled homomeric and hybrid capsules

Abstract: We present here the reversible, guest-controlled disproportionation of homomeric and hybrid capsules using photochemistry. The supramolecular containers are self-assembled from shallow and deep cavitand modules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Whilst self‐assembly of discrete supramolecular architectures has reached some extraordinary heights in terms of sheer size of assembly product, there are still many open questions regarding how best to develop assemblies that respond to their environment and reversibly switch between assembly states. Along these lines of thought, Rebek has shown that both photochemical switching of an azobenzene guest, or the addition of a second type of assembly subunit, can induce assembly switching in a supramolecular host . Similarly, Nitschke and Schalley have reported how mixing two homoleptic Zn 4 L 6 tetrahedra forms a dynamic combinatorial library that can be controlled by the choice of added guest .…”
Section: Figurementioning
confidence: 99%
“…Whilst self‐assembly of discrete supramolecular architectures has reached some extraordinary heights in terms of sheer size of assembly product, there are still many open questions regarding how best to develop assemblies that respond to their environment and reversibly switch between assembly states. Along these lines of thought, Rebek has shown that both photochemical switching of an azobenzene guest, or the addition of a second type of assembly subunit, can induce assembly switching in a supramolecular host . Similarly, Nitschke and Schalley have reported how mixing two homoleptic Zn 4 L 6 tetrahedra forms a dynamic combinatorial library that can be controlled by the choice of added guest .…”
Section: Figurementioning
confidence: 99%
“…Et), was synthesized with low efficiency via NvN coupling. 18 In contrast, 6kd was obtained in a high yield of 95% through our method. These results show that the C-N coupling strategy is an efficient way to assemble symmetrical and unsymmetrical aromatic azo derivatives, circumventing the formation of homocoupled azo by-products.…”
Section: Resultsmentioning
confidence: 77%
“…Trans -azobenzenes 1 – 5 (Figure ) were synthesized, purified, and characterized by methods reported in the literature. , Complexation of 1 – 5 with OA in aqueous solution was achieved as outlined in the Supporting Information. Characteristic changes in the 1 H NMR signals of the host OA and the upfield shifts of the signals due to para -alkyl groups (CH 2 and CH 3 ) of the guest (note signals in the region of δ 5.5–8 and below 0 ppm, respectively, in Figure ) in the Na 2 B 4 O 7 –D 2 O solution containing 1 – 5 and OA confirmed the inclusion of the former within OA. , The continuous change in the 1 H NMR spectra with addition of the guest to the OA solution that ended with 0.5 equiv of the guest suggested ABs formed stable 1:2 complexes with OA (guest@OA 2 ) (Figures S1–S5).…”
mentioning
confidence: 84%